Desarrollo de una bebida alcohólica a partir de cubio (Tropaeolum tuberosum Ruiz & Pav.) empleando levadura de Saccharomyces bayanus - Morantes Triana , Martha; Lopez Molinello, Alfredo; Prieto, Lena; Povea, Ismael; Saenz, Santiago (Ingeniería, 2024)
Context: Cubio (Tropaeolum tuberosum), an ancestral tuber cultivated in select regions of Colombia, possesses significant nutritional value but remains a marginalized crop. This study aims to enhance the recognition of cubio by diversifying its applications through the production of a fermented alcoholic beverage. Method: Initially, the cubio tuber was characterized. A concentrated and enzymatic pretreatment utilizing alpha-amylase and glucoamylase was employed to release sugars. Afterwards, fermentation was carried out, using Saccharomyces bayanus in a carefully controlled bioreactor setting. The fermentation medium was composed of 0.1% (NH4) H2PO4, 0.3% MgSO4, 0.5% peptone, and 0.3% yeast extract, with the aim of reaching an alcohol content of 15 °GL. The bioreactor was inoculated with Saccharomyces bayanus at 25 °C, maintaining a pH of 5.2 and an agitation speed of 100 rpm. Daily monitoring of pH levels, sugar concentrations, and biomass was conducted over a 15-day period. Finally, the physicochemical properties, physical attributes, and sensory qualities of the resulting product were assessed. Results: The analysis of the cubio tuber revealed the presence of 2.18 ± 0.002% reducing sugars, 4.48 ± 0.064% proteins, and 1.66 ± 0.015% starch. Throughout the fermentation process, the yeast exhibited a growth rate of 2.3786 mg.L-1.day-1. As a result, the concentration of reducing sugars decreased to 15.45 mg.L-1.day-1, and an alcohol production of 1.1786 ºGL.day-1 was observed. The final alcoholic beverage contained 15.24 °GL, with a pH of 4.5 and a total acidity of 7.21 ± 0.029 g. L-1. Additionally, an expert panel positively rated the flavor and aroma of the beverage. Conclusion: It is technologically possible to produce a fermented alcoholic beverage of adequate quality from the cubio tuber, implying an alternative use for this ancestral crop.